“What Is Jewish Philosophy? An Attempt at a Definition Based On Jerusalem (1783) By Moses Mendelssohn - Delambre, Anaïs-Rivka (Con-Textos Kantianos. International Journal of Philosophy, 2025)
In this article, we look at the definition of “Jewish philosophy”, a concept whose contours remain unclear. Does the term simply refer to the cultural or religious affiliation of the philosophers concerned, or is there something in their philosophy itself that qualifies it as Jewish? To answer this question, we have drawn on the reflections of Eliezer Berkovits, who has defined Jewish philosophy as the incorporation of philosophical concepts and reasoning into a distinct Hebraic framework of thought and tradition. Using Mendelssohn’s Jerusalem as a case study, we refine and extend the concept of incorporation to show that Jewish philosophy is articulated between the universality of philosophical thought and the particularity of Jewish tradition.